Structure and electronic properties of Si-doped CeO2 (111) surface by the first principle method. (September 2018) - Jia, Huiling; Ren, Baogen; Li, Mei; Liu, Xuejie; Wu, Jinxiu; Tan, Xin
Abstract: This study aimed to determine the effects of Si doping in CeO2 (111) surface on the polishing performance. For this purpose, the structure and electronic properties of pure CeO2 (111) surface and Si-doped surface were calculated and compared by the first principles based on density functional theory. The reduction capabilities of the two surface systems were analyzed. Calculated results demonstrate that the ionic structure of Si-doped surface presents a symmetric change and that the formation energy of surface O vacancy decreases by 1.388 eV, indicating that Si doping is conducive for the reduction in surface system. Two electrons left by the O vacancy in the reduction system are obtained by the nearest 2 Ce 4+, and the Ce 4+ are reduced to Ce 3+ . After Si doping, the hybridization state between Si ion and adjacent Ce and O ions occurs at the Fermi level. Therefore, the synergistic effect of Si doping and O vacancy can enhance the reactivity of CeO2 polishing particle surface. Highlights: The structure change in Si-doped CeO2 (111) surface was obtained using DFT. The effect of Si doping on reduction property of CeO2 (111) surface was determined. DOS and charge density difference of Si-doped CeO2 (111) surface was analyzed.